JURIDICAL ANALYSIS OF CRIMINAL ACTIONS CONFLICT AGAINST CHILDREN IN JAYAPURA CITY - Ingratubun, Fitriyah (Universitas Bengkulu, 2023)
Criminal activity is defined as an act that is prohibited by law and is accompanied by threats or consequences in the form of certain punishments. A criminal act can also be defined as an activity that is prohibited and threatened by a legal rule, as long as the prohibition is aimed at an act, namely a situation or event created by the person who caused the event to occur. The legal research approach used in this research is research that explores legal problems that actually exist in society and is based on field data that is linked to the subject matter being studied. The research results showed that the application of the criminal law for sexual intercourse with children in imposing sentences on perpetrators of criminal acts of sexual intercourse committed by adults against children in reality rarely found perpetrators who were sentenced to the maximum sentence, in fact more perpetrators were sentenced to less than half. the maximum penalty stipulated in law. This indicates that the role of the judiciary in providing a deterrent effect against perpetrators is still half-hearted, this is also one of the reasons why many people are not afraid to commit the crime of sexual intercourse with children. The judge's consideration in imposing a crime on the perpetrator of sexual intercourse is that it must include the basis of the trial, the basis of the decision and the values that exist in society. Keywords: Children, Crime, Sexual Intercourse